If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x-13=x+23
We move all terms to the left:
4x-13-(x+23)=0
We get rid of parentheses
4x-x-23-13=0
We add all the numbers together, and all the variables
3x-36=0
We move all terms containing x to the left, all other terms to the right
3x=36
x=36/3
x=12
| x^2-10x+2000=0 | | 4x+3=1/3(12x+9) | | 50k+5=4+16k | | 13c-12=15c-16 | | 7x12=-47 | | 11=9z+2z | | 2x+5=- | | 7/3=2x+15/x | | p−316=−212 | | 1=(x-4)/2 | | 8=c/2+7 | | 10y^2+27y-9=0 | | -632c-7=5c | | (x-19)/3=-6 | | 4(y+2)-2(5-3y)=8 | | 13c–12=15c–16 | | 24=2(1+t) | | (x+12)/7=-2 | | 20+12u+18=-7+3u | | 3+4m=12-2m | | -12+5k=-9 | | -1=d/5 | | -1=d5 | | -2(-4-6x)=-10+3 | | 2(3y+4+2)=196−16 | | 4x+17=2(3x-8)+x | | 2z/9-4=-1 | | 14+5n=-4n+16 | | 3+4y=16 | | -2=z6 | | 2x+45=47 | | 54=7+x16 |